2008
DOI: 10.1007/s11604-008-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dose distribution between carbon ion radiotherapy and photon radiotherapy for head and neck tumor

Abstract: CIRT has the potential to improve the target dose conformity, inhomogeneity coefficient, and OAR sparing when compared with 3D-CRT and IMRT. Compared with 3D-CRT, normal tissue exposure was reduced mainly in the mid-to low-isodose levels using IMRT. Additional improvement was obtained using CIRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Previous experience has demonstrated that more effective dose distributions in terms of vital tissue sparing can be achieved with IMCT compared with IMRT in patients with head and neck cancer . However, to the best of our knowledge, CIRT has never been used in the treatment of patients with LR‐NPC, and there is no literature to date suggesting the proper dose of CIRT to be used for reirradiation in patients with head and neck cancer recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experience has demonstrated that more effective dose distributions in terms of vital tissue sparing can be achieved with IMCT compared with IMRT in patients with head and neck cancer . However, to the best of our knowledge, CIRT has never been used in the treatment of patients with LR‐NPC, and there is no literature to date suggesting the proper dose of CIRT to be used for reirradiation in patients with head and neck cancer recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated beams of heavy, charged particles and protons have a finite range and a distant Bragg peak . Dosimetry studies have shown that carbon ion RT (CIRT) enables the delivery of high‐dose RT to the target volume(s) while sparing organs at risk (OAR), thereby enhancing the therapeutic ratio over IMRT in patients with head and neck cancer . Early data also have suggested that the use of proton or heavy ion (noncarbon) RT for patients with LR‐NPC is feasible and potentially effective …”
Section: Introductionmentioning
confidence: 99%
“…In three-dimensional conformal radiotherapy and intensity modulated radiotherapy, low-dose regions are generally enlarged because multi-portals are used to ensure conformable dose distribution to the target. On the other hand, C-ion RT can deliver conformable dose distribution to the target without expanding the low-dose regions [13]. Therefore, the maxilla volumes irradiated at low doses in C-ion RT might actually correlate with those receiving higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who receive a combined dose above 100 Gy from initial RT and re-irradiation may have a higher chance of developing SAEs including cranial neuropathy, brain injury, mucosal necrosis and massive hemorrhage, which could result in significantly reduced quality of life, or even death. Because most of its energy is deposited in the region called “Bragg peak”, CIRT is able to accurately deliver high-dose radiation to the tumors while sparing surrounding organs 6 , 24 . Meanwhile, the higher relative biological effectiveness of accelerated carbon-ion beams enable more effective elimination of resistant tumors cells frequently appeared in LR-NPC 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%